2010
DOI: 10.2298/abs1001185k
|View full text |Cite
|
Sign up to set email alerts
|

Comparative in vitro anthelmintic activity of three plants from the Amaranthaceae family

Abstract: The three plants presented in this study are Amaranthus spinosus, Amaranthus caudatus and Amaranthus viridis L. They belong to the Amaranthaceae family and are traditionally used as vermicides. Our aim was to investigate the anthelmintic activity of the three plants using earthworms (Pheretima posthuma). Methanol extracts of the three plants at different concentrations (10, 20, 40, 60, 80, 100 mg/ml) showed dose-dependent vermicidal activities. At concentrations of 80 and 100 mg/ml all three plant extracts cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 19 publications
0
36
0
1
Order By: Relevance
“…The Anthelminthic activity [16][17][18] was carried out using adult earthworms (pheretima posthuma), belongs to the group of Annelida. 20ml of aqueous methanolic(50:50) extract of caralluma attenuata (test solutions) containing three different concentrations (100mg/ml, 200mg/ml, and 300mg/ml in distilled water) were prepared and taken in three different petridishes and 5 earthworms were placed in each petridish.…”
Section: Anthelminthic Activitymentioning
confidence: 99%
“…The Anthelminthic activity [16][17][18] was carried out using adult earthworms (pheretima posthuma), belongs to the group of Annelida. 20ml of aqueous methanolic(50:50) extract of caralluma attenuata (test solutions) containing three different concentrations (100mg/ml, 200mg/ml, and 300mg/ml in distilled water) were prepared and taken in three different petridishes and 5 earthworms were placed in each petridish.…”
Section: Anthelminthic Activitymentioning
confidence: 99%
“…In a search for larvacidal activity one study found β-sitosterol (17-(5-Ethyl-6-methylheptan-2-yl)-10,13-dimethyl-2, 3,4,7,8,9,11,12,14,15,16,17 dodecahydro-1H cyclopenta [a]phenanthren-3-ol) and plumbagin. The study had utilized column chromatography and1D, 2D NMR to find out these compounds [12].…”
Section: Chemistry Of Plumbago Zeylanica Lmentioning
confidence: 99%
“…When anthelmintic drug is administered sequentially, it eliminates susceptible helminthes without affecting for parasites that are resistant. The resistant parasites in turn pass their resistant genes on to the next generation of worms [3].The majority of diseases caused by helminthes are persistent, weakening nature; and probably cause more morbidity and greater economic and social deprivation among humans and animals than any single group of parasites [4].Therefore, unless drugs especially those synthetic origin are modified or substituted by plant origin drugs with the same or higher potency, drug resistance will be unmanageable. Especially in developing countries like Ethiopia the issue is even more critical.…”
Section: Introductionmentioning
confidence: 99%
“…Anthelmintics from natural sources could play a key role in the treatment of these parasite infections. Hence there is an increasing demand towards natural anthelmintics (Kumar et al, 2010). Antiemetics are typically used to treat motion sickness and the side effects of opioid analgesics, general anaesthetics, and chemotherapy directed against cancer (Fake et al, 2004;Sontakke and Thawani, 2003).…”
Section: Introductionmentioning
confidence: 99%